HUBUNGAN POWER OTOT LENGAN DAN BAHU DENGAN HASIL LEMPAR LEMBING SISWA PUTRA KELAS X TKBB SMKN 5 PEKANBARU. - indra, Surya; ', ramadi; Agust, 2Kristi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This problem in this study is still the numbers of students who failed in achieving the target in the javelin average only reach distance± 17 meter, while the desired distance according KKM is 20 meter. This study aims is to determine whether there is a corelation of our arm muscle and houlders with the results thrown spear the student’s class X TKBB SMK Negeri 5 Pekanbaru . Sample collections tecnique is total sampling the population of this study are a male students of class X TKBB SMK Negeri 5 Pekanbaru, the sample of this study were male students of class X TKBB SMK Negeri 5 Pekanbaru with the numbered of students are 13 students. This research using a correlation technique. Then, the data are tested using the test of normality, test the product moment correlation test, test of significance on the level of significance of α = 0.05. Test of normality of variabels X, L0maks (0,149) < Ltabel (0,234), and testing normality of variabels Y, L0maks (0,204) < Ltabel (0,234) in other words at a of normal data and concluded the results showed: there is a relationship between of our arm muscle and houlders with the results thrown spear, with correlation r= 0.224, where the large correlation coefficient when viewed from the level of relationship(interpretation) r value is to low level of relationship with interpretation r velue 0,20 – 0,399.Key Words: The Power Arm Muscles And Shoulder With The Results Of Javelin